Engineering of Phenotypically Distinct Human Cartilage Microtissues for the Biofabrication of Zonally Defined Articular Cartilage Grafts - Rodriguez, Nadia (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2025)
Articular cartilage damage does not self-repair, leading to further joint degeneration and ultimately the development of osteoarthritis. Tissue engineering has made important progress in the development of functional cartilage grafts, but true joint regeneration remains elusive. While a cartilage-like tissue is often developed, a fibrocartilaginous or hypertrophic cartilage phenotype is commonly observed. In addition, current approaches fail to recapitulate the complex zonal organisation of the native tissue, which is defined by spatial gradients in tissue composition and architecture. Developmentally inspired tissue engineering strategies have emerged as an alternative to regenerate articular cartilage by mimicking key steps of normal tissue development. Stem or progenitor cells can self-organise to generate microtissues or organoids, which can be used as biological building blocks to fabricate larger grafts of clinically relevant size. The objective of this thesis was to use adult human stem/progenitor cells, which are a clinically relevant source of cells, to engineer phenotypically distinct hyaline cartilage microtissues for the modular assembly of zonally organised grafts. To this end, human articular cartilage progenitors (hACPs) or bone marrow-derived mesenchymal stem/stromal cells (hMSCs), altered oxygen levels and gene silencing therapy were explored to enhance the function of human cell-derived microtissues. Melt electrowritten (MEW) meshes were then used to guide the fusion of such microtissues and support the development of scaled-up grafts. It was demonstrated that hACPs cocultured with hMSCs supported the deposition of type II collagen. In addition, hMSC-derived microtissues differentiated at altered oxygen levels, representative of the levels found in the different regions of the native tissue, resulted in distinct cartilaginous phenotypes, whose composition resemble the superficial and deep regions of native articular cartilage. Lower oxygen (2% O2) significantly enhanced the deposition of glycosaminoglycans compared to higher oxygen (5% O2). Such microtissues were then fused onto a MEW mesh and allowed to generate a larger graft with controlled geometry. This guiding MEW mesh was found to support the development of a tissue with a collagen network somewhat mimetic of the native tissue. Finally, transfection with the pro-chondrogenic gene therapeutic, anti-miR-221, in hMSC-derived microtissues was found to significantly enhance the deposition of type II collagen with no signs of early hypertrophy. In conclusion, this thesis highlights the potential of hMSC-derived cartilage microtissues as biological building blocks for the biofabrication of articular cartilage grafts.
APPROVED
Keywords: Modular Assembly; Gene Silencing; Mesenchymal Stem/Stromal Cells; Microtissues; Hyaline Articular Cartilage; Oxygen; MEW; Anti-miR-221; Progenitor Cells; Tissue Engineering